Records from Bethlem Royal Hospital, 1559-1932. - Bethlem Royal Hospital (London, England); Bethlem Museum of the Mind; Findmypast Ltd (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2022)
Bethlem Royal Hospital is a psychiatric facility in London. It was established as a priory of the Order of St Mary of Bethlehem in 1247, before beginning to care for mentally ill patients sometime in the 14th century. Often referred to colloquially as ‘Bedlam’—and generally accepted to be the origin of the very same noun—past incarnations of the institution were infamous for their questionable diagnosis of mental illness and poor treatment of patients. This collection, which has been curated in association with Findmypast and the Museum of the Mind, contains four centuries and 130,000 images worth of records from Bethlem. The records are diverse in both form and subject matter. They include: voluntary and criminal admission registers; discharge and death registers; male and female patient casebooks; minutes of the Court of Governors; and staff salary books. All handwritten items have been fully transcribed.
Date range: 1559-1932.
Keywords: Bethlem Royal Hospital (London, England) -- History -- Sources; Mental illness -- Treatment -- Great Britain -- History; Bethlem Royal Hospital (London, England) -- Records and correspondence